Nasal Endoscope: An Armamentarium in the Management of Sinonasal Inverted Papilloma - Kadapa, Nagendra P. B. (Springer India, 2014)
Sinonasal inverted papillomas (SIP) are unique group of locally aggressive benign neoplastic lesions arising from mucosa of sinonasal tract with potential for recurrences and known association with squamous cell carcinoma in 5–15 % of cases. This study was conducted was to assess the efficacy and usefulness of the nasal endoscope in treating SIP. We reviewed 28 biopsy proven cases of SIPs that were treated at our hospital between June 2009 and September 2013. Average patient age was 46 years. Fourteen were treated by transnasal endoscopic excision of tumor with noted recurrence of 21.43 %. Thirteen were treated by endoscopic assisted open surgery which had 23 % recurrence. Three patients had malignant inverted papillomas, of whom two (7 %) were found to have synchronous squamous cell carcinoma and one (3.6 %) had metachronous squamous cell carcinoma. No evidence of recurrence was found in rest during our follow up. The endoscopic approach is the preferred method for the treatment of the majority of inverted papillomas. Powered instrumentation is extremely useful to achieve good results. Although significant number of cases was done by external approach by lateral rhinotomy, the endoscopic assistance is required to ensure complete removal of the tumour to reduce the recurrence rates. Close follow up of the patient for a longer period of time is necessary for the early detection of recurrence and to allow for surgical salvage.